Uterine infection alters the transcriptome of the bovine reproductive tract three months later. Issue 1 (July 2020) - Horlock, Anthony D; Piersanti, Rachel L; Ramirez-Hernandez, Rosabel; Yu, Fahong; Ma, Zhengxin; Jeong, KwangCheol C; Clift, Martin J D; Block, Jeremy; Santos, José E P; Bromfield, John J; Sheldon, I Martin
Abstract : Infection of the postpartum uterus with pathogenic bacteria is associated with infertility months later in dairy cattle. However, it is unclear whether these bacterial infections lead to long-term changes in the reproductive tract that might help explain this infertility. Here we tested the hypothesis that infusion of pathogenic bacteria into the uterus leads to changes in the transcriptome of the reproductive tract 3 months later. We used virgin Holstein heifers to avoid potential confounding effects of periparturient problems, lactation, and negative energy balance. Animals were infused intrauterine with endometrial pathogenic bacteria Escherichia coli and Trueperella pyogenes ( n = 4) and compared with control animals ( n = 6). Three months after infusion, caruncular and intercaruncular endometrium, isthmus and ampulla of the oviduct, and granulosa cells from ovarian follicles >8 mm diameter were profiled by RNA sequencing. Bacterial infusion altered the transcriptome of all the tissues when compared with control. Most differentially expressed genes were tissue specific, with 109 differentially expressed genes unique to caruncular endometrium, 57 in intercaruncular endometrium, 65 in isthmus, 298 in ampulla, and 83 in granulosa cells. Surprisingly, despite infusing bacteria into the uterus, granulosa cells had more predicted upstream regulators of differentially expressed genes than all the other tissues combined. In conclusion, there were changes in the transcriptome of the endometrium, oviduct and even granulosa cells, 3 months after intrauterine infusion of pathogenic bacteria. These findings imply that long-term changes throughout the reproductive tract could contribute to infertility after bacterial infections of the uterus.